2020
DOI: 10.3389/fpsyt.2020.00255
|View full text |Cite
|
Sign up to set email alerts
|

Classification Methods Based on Complexity and Synchronization of Electroencephalography Signals in Alzheimer’s Disease

Abstract: Electroencephalography (EEG) has long been studied as a potential diagnostic method for Alzheimer's disease (AD). The pathological progression of AD leads to cortical disconnection. These disconnections may manifest as functional connectivity alterations, measured by the degree of synchronization between different brain regions, and alterations in complex behaviors produced by the interaction among widespread brain regions. Recently, machine learning methods, such as clustering algorithms and classification me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 82 publications
1
50
0
1
Order By: Relevance
“…The subjects of this study were 16 patients with AD and 18 sexmatched and aged-matched healthy old individuals (see Table 1) (Mizuno et al, 2010;Nobukawa et al, 2019Nobukawa et al, , 2020. The sample size of AD and HC groups was determined based on previous works on complexity analysis (Abásolo et al, 2008;Mizuno et al, 2010;Nobukawa et al, 2019Nobukawa et al, , 2020. For this study, we defined healthy old individuals as nonsmokers and not on medication.…”
Section: Subjectmentioning
confidence: 99%
See 2 more Smart Citations
“…The subjects of this study were 16 patients with AD and 18 sexmatched and aged-matched healthy old individuals (see Table 1) (Mizuno et al, 2010;Nobukawa et al, 2019Nobukawa et al, , 2020. The sample size of AD and HC groups was determined based on previous works on complexity analysis (Abásolo et al, 2008;Mizuno et al, 2010;Nobukawa et al, 2019Nobukawa et al, , 2020. For this study, we defined healthy old individuals as nonsmokers and not on medication.…”
Section: Subjectmentioning
confidence: 99%
“…Positron emission tomography (PET) and magnetic resonance imaging (MRI) are often used to diagnose AD and detect neurotransmitter activity disorders, amyloid beta plaque deposition, and brain atrophy (Ewers et al, 2011;McKhann et al, 2011;Sperling et al, 2011). As methods focused on functional neural activity, studies based on the temporal behavior of neural activity were conducted using electroencephalography (EEG), magnetoencephalography (MEG), and functional magnetic resonance imaging (fMRI) (Greicius et al, 2004;Jeong, 2004;Stam, 2005;Dickerson and Sperling, 2008;Takahashi, 2013;Yang and Tsai, 2013;Wang et al, 2017;Nobukawa et al, 2020). Among all these evaluations, EEG is cost-effective, widely available, and non-invasive, making it ideal for clinical applications (Vecchio et al, 2013;Kulkarni and Bairagi, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies repeatedly demonstrated that patients with Alzheimer's disease show an increase in delta/theta band power, a decline in alpha/beta band power, reduced complexity and impaired synchrony in EEG signals compared to non-Alzheimer individuals (Dauwels et al, 2010;Nobukawa et al, 2019Nobukawa et al, , 2020Smailovic and Jelic, 2019), there have been limited data on assessing the EEG signals associated with neuropsychiatric conditions for Alzheimer's patients with the same severity of dementia. While neuropsychiatric symptoms generally increase as the stage of dementia progresses, many symptoms still develop in the early stage of Alzheimer's disease (Panza et al, 2010;Lyketsos et al, 2011;Hashimoto et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the behavioral and psychological symptoms vary to an extent among Alzheimer’s patients even though if they have the same severity of dementia, understanding the variation should help initiate preventive measures, organize appropriate care, and facilitate applicable treatment plans for these patients. While previous studies had examined the difference in EEG signals of Alzheimer’s patients vs. non-Alzheimer’s patients recognizing alternation of EEG power, and/or reduction of temporal complexity and functional connectivity in Alzheimer’s disease (Dauwels et al, 2010 ; Nobukawa et al, 2019 , 2020 ; Smailovic and Jelic, 2019 ), this study aimed to explore the potential difference in EEG scans of heterogeneous Alzheimer’spatients. Our hypothesis was that between patients with the same severity of disease, there would still be a difference in their neuropsychiatric symptoms with a corresponding difference in their EEG signals.…”
Section: Introductionmentioning
confidence: 99%